Models of coexistence: approaches for overcoming the classical legal division between the "Land of Islam" and the "Land of War" by contemporary Islamic scholars - Bork, Johannes (Journal of beliefs and values, 2017)
This article aims to present contemporary interpretations of the territorial division between the Abode of Islam and the Abode of War in classical Islamic legal theory, with a focus on perspectives that try to overcome outdated concepts and suggest suitable alternatives. Towards this end, it presents approaches from two modern Muslim scholars - the Swiss intellectual Tariq Ramadan and the Syrian academic Wahbah al-Zuhaili - that offer different perspectives on the notion of the two abodes. They both attempt to mould new models that consider the current circumstances, while trying to develop a vision of coexistence between Muslims and non-Muslims that is firmly based on Islamic law. Finally, there is an evaluation of the two positions and their arguments, so as to conclude which one of them offers objectives that are better suited to the needs of modern Muslim societies.